A disease‐specific decline of the relative abundance of Bifidobacterium in patients with autoimmune hepatitis. Issue 12 (7th May 2020) - Liwinski, Timur; Casar, Christian; Ruehlemann, Malte C.; Bang, Corinna; Sebode, Marcial; Hohenester, Simon; Denk, Gerald; Lieb, Wolfgang; Lohse, Ansgar W.; Franke, Andre; Schramm, Christoph
Summary: Background: The pathogenesis of autoimmune hepatitis (AIH) is poorly understood and little is known about enteric microbiota in AIH. Aim: To investigate disease‐specific microbiome alterations in AIH. Methods: The V1‐V2 variable regions of the 16S rRNA gene were sequenced in faecal samples from 347 patients with AIH and controls (AIH n = 72, healthy controls (HC) n = 95, primary biliary cholangitis (PBC) n = 99 and ulcerative colitis (UC) n = 81). Results: Biodiversity (Shannon entropy) was decreased in AIH patients compared to HC ( P = 0.016), which was partially reversed by azathioprine ( P = 0.011). Regarding between‐sample diversity, AIH patients separated from HC, PBC and UC individuals (all P = 0.001). Compared to HC, decreased relative abundance of anaerobic genera such as Faecalibacterium and an increase of Veillonella and the facultative anaerobic genera Streptococcus and Lactobacillus were detected. Importantly, a disease‐specific decline of relative abundance of Bifidobacterium was observed in AIH patients. Lack of Bifidobacterium was associated with failure to achieve remission of AIH ( P < 0.001). Of potential therapeutic implication, Bifidobacterium abundance correlated with average protein intake ( P < 0.001). Random forests classification between AIH and PBC on the microbiome signature yielded an area under receiver operating characteristic curve (AUC) of 0.787 in the training cohort, and an AUC of 0.849 in an external validation cohort. Conclusion: Disease‐specific faecal microbial alterations were identified in patients with AIH. Intestinal dysbiosis in AIH was characterised by a decline of Bifidobacterium, which was associated with increased disease activity. These results point to the contribution of intestinal microbiota to AIH pathogenesis and to novel therapeutic targets.